(untitled) (Global Journal of Science Frontier Research, 2015)
This paper presents a brief modern physics teaching proposal for high school students, with a view to the importance of the use of experiments and simulations. With this is expected to facilitate the teaching and learning of students with respect to modern physics subject, which is not very well seen in high school, is of great importance to the education of the student. I also hope that this work will serve as an aid for teachers in order to view and teaching of modern physics in secondary level schools.